Development of a framework to capture the maturity of food safety regulatory and enforcement agencies: Insights from a Delphi study. (December 2022) - Nayak, Rounaq; Jespersen, Lone
Abstract: Purpose: The purpose of the paper is to present the first stage of work being undertaken to develop and evaluate a maturity framework designed to assess and benchmark the effectiveness, ability to achieve continuous improvement, and optimise processes and functioning of food safety regulatory and enforcement agencies across the world. Design/Methodology: To achieve this aim, a comparison of global food safety regulations, and Delphi-interviews with stakeholders of food safety regulatory and enforcement agencies from Australia, Canada, Ireland, and USA were carried out. Through inductive, textual data analysis, three dimensions and thirteen sub-dimensions were identified that covered cultural and systems elements influencing the quality and impact of food safety regulations across the world as well as the gaps identified by the stakeholders. Findings: The conclusions of the paper are that whilst there is broad support by food safety regulators for developing a benchmarking and evaluation framework for food safety regulatory and enforcement agencies, there are also some outstanding challenges such as defining globally applicable measures, buy-in from specialised agencies and senior management to adopt a maturity framework to change the culture within regulatory agencies, and the role played by governments in influencing the efficiency and functioning of regulatory systems. Limitations/Implications: While more research would be required to further develop a maturity scale to assess food safety regulatory and enforcement agencies, it is concluded that evaluating the maturity of food safety regulatory and enforcement agencies (FSRA) by food safety regulators is a realistic possibility but needs to take account of some of the lessons which could be learnt from guidance frameworks with similar goals (e.g., the Food and Agriculture Organization's Food Control System Assessment Tool). Evaluation of the framework should be carried out by national agencies to develop a user-centred maturity toolkit. Highlights: Food safety regulators' perspectives on the building blocks of agencies were identified. Actions required to help agencies evolve into mature organisations were explored. Globally applicable model to capture the maturity of food safety agencies was developed. Diverse regulatory and enforcement practices of agencies were identified. Challenges faced by agencies and their impact on public health and trade were identified.